97 Multi-vessel Angioplasty at the Time of STEMI has Equivalent Mortality to a Culprit Only Strategy: Resolving The Paradox of Randomised Controlled Trials and Observational Studies in Multivessel Disease and STEMI. (3rd June 2016) - Ahmad, Yousif; Cook, Chris; Petraco, Ricardo; Nijjer, Sukhjinder; Al-Lamee, Rasha; Shun-Shin, Matthew; Keene, Daniel; Balu, Ashwin; Malik, Iqbal; Baker, Christopher; Mikhail, Ghada; Sethi, Amarjit; et al.
Abstract : Background: Patients with ST-elevation myocardial infarction commonly have multi-vessel disease. After treating the culprit, the optimal strategy for residual disease is unknown. Large observational studies suggest deferring treatment of residual disease, but smaller randomised controlled trials (RCTs) suggest multi-vessel primary percutaneous coronary intervention (MV-PPCI) is safe. We examine if allocation bias of high-risk patients could explain conflicting results between observational studies and RCTs. Methods: A meta-analysis of registries comparing culprit-only PPCI to MV-PPCI was performed. A meta-regression was performed to determine if allocation bias of high-risk patients could explain differences in outcomes between therapies. Results: 47, 717 patients (19 studies) were eligible. MV-PPCI had higher mortality than culprit-only PPCI (OR 1.59, 95% CI 1.12 to 2.24, p = 0.03). Higher risk patients were more likely to be allocated to MV-PPCI (OR 1.45, 95% CI 1.18 to 1.78, p = 0.0005). When this was accounted for, there was no difference in mortality (OR 0.99, 95% CI 0.69 to 1.41, p = 0.94). Discussion: Clinicians preferentially allocate higher-risk patients to MV-PPCI at the time of STEMI. When this is accounted for, these large observational studies in 'real world' patients support the conclusion of the smaller RCTs in the field: MV-PPCI has equivalent mortality to a culprit-only approach.